(untitled) - Clifford, Christine (Hoboken, 2013)
Let's Close a Deal articulates the intuitive process that identifies how and why a deal will appeal, and then demonstrates in step-by-step detail how to present your deal in a compelling way. The sales process is not about coercion; it's about compassion. The closing part of a negotiation should honor everyone involved instead of taking advantage of them.
Keywords: Selling,Bán hàng